PENGGUNAAN PEKTIN KULIT KAKAO SEBAGAI EDIBLE COATING DAN PEMBEKUAN KRIOGENIK UNTUK MEMPERTAHANKAN KRISTALISASI FRUIT PLATTER - Ananda, Rifky Dwi; Wardani, Anisya Mutiara; Shafira, Kesya Khansa; Aini, Nur (Universitas Sebelas Maret (UNS), 2022)
One of the sensational foods is a fruit platter or fruit cuts that is crystallized so when the fruit is consumed it can make a tickling sound. However, the process of making fruit platters in this way is still not effective, sugar as a coating is easy to melt when the water inside the fruit comes out due to different osmotic pressures, so the shelf life is not long, and the nutritional content is decreases due to chilling injury in normal freezer. Considering this problem, we make a research to apply pod husk cocoa pectin as an edible coating on fruit platter, and low temperature treatment, as well as storage in vacuum packaging to minimize physical injury, chemical nutrient and sensory decreasing, and sensory of the fruit platter.This experimental research method is using RAL. The first factor is concentration of cocoa pectin with 3 levels, there are 1%, 2%, and 3% pectin. The second factor is the freezing method with 3 levels, there are cryogenic freezing with chest freezer storage, chest freezer freezing, and room temperature storage. The third factor is the type of vacuum packaging with 3 levels, there are polyethylene, polypropylene, and polypropylene aluminum plastic packaging. From the results of this research we know that methoxyl levels and galacturonic acid levels are 4.65% and 48.5%. The results of the physicochemical analysis of the fruit platter are, weight loss ranged from 1.13%, pH to 3.69 and 4.43, decreased water content was 0.33%-0.07%%, texture was decreased, the average was 0.19. Also organoleptic analysis for each attribute was significantly different from the control treatment. Until 10th day of storage, the taste, texture, color and aroma of the fruit remained fresh, so it is still acceptable to the panelists.